HADIS DAN KESARJANAAN TIMUR - Alwy Fadly Harahap (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
Goldziher''s view of hadith is that most hadiths cannot be trusted as a whole as a source of teachings sourced from the Prophet. Most of the hadith material in the hadith book collection is sourced from the results of the religious, historical and social development of Islam which is sourced from hadith figures in the first two centuries. Library research called the scholar skeptic as a scholar who analyzed the problem of authenticity of hadith as a scholar who used an